3-(Adamantan-1-yl)-4-benzyl-1H-1,2,4-triazole-5(4H)-thione - A. M. Al-Omary, Fatmah; A. Ghabbour, Hazem; El-Emam, Ali A.; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
The title compound, C19H23N3S, is a functionalized triazoline-3-thione derivative. The benzyl ring is almost normal to the planar 1,2,4-triazole ring (r.m.s. deviation = 0.007 A°) with a dihedral angle of 86.90 (7)°. In the crystal, molecules are linked by pairs of N—H...S hydrogen bonds, forming inversion dimers that enclose R2/2(8) loops. The crystal packing is further stabilized by weak C—H...n interactions that link adjacent dimeric units into supramolecular chains extending along the a-axis direction.